The Effect of Perceived Convenience, Perceived Usefulness and Trust on Interest in Using Electronic Wallets at the Muhammadiyah University of Sidoarjo - Anisa Ayu Karindra; Dewi Komala Sari (Indonesian Journal of Islamic Studies, 2023)
In this regard, the payment system used by the community is also developing. Currently, the payment system is not only in the form of physical (cash) but there is already technology that can replace money into an intangible (non-cash) commonly called electronic money. OVO is an application that can be used to make purchase or payment transactions. The purpose of this study is to determine the influence of perceptions of convenience, perception of usability, and trust both partially and simultaneously on the interest in using the OVO application at the University of Muhammadiyah Sidoarjo.This research uses quantitative data. And samples were taken as many as 100. The data analysis technique in this study uses data processing assistance from IBM SPSS version 25 software. The tests carried out are validity test, reliability test, classical assumption test which includes normality test, linearity test, autocorrelation test, heteroscedasticity test, and multicollinearity test, then using multiple linear regression analysis, hypothesis testing includes t-test and f-test, then the multiple correlation coefficient and multiple determination coefficients are tested.The results of the study prove that Perceived Ease Of Use affects intention to use, perceived usefulness affects intention to use, Trust affects intention to use, as well as intention to use, perceived usefulness, and trust simultaneously affect intention to use of OVO application users at University of Muhammadiyah in Sidoarjo.